BREAST CANCER IN WOMEN WITH DIABETES MELLITUS TYPE 2 - Vatseba, T.S.; Sokolova, L.K. (World of Medicine and Biology, 2019)
Prevalence of breast cancer in the women with diabetes mellitus type 2 and the effect of hypoglycemic therapy on the frequency of the cancer and survival rates were studied. A significantly higher risk of breast cancer was detected in the women with type 2 diabetes mellitus [OR = 3.30; 95% CI (2.59-4.22) p
Keywords: diabetes mellitus; cancer risk; breast cancer; survival rate of patients